MiRNA-17 encoded by the miR-17-92 cluster increases the potential for steatosis in hepatoma cells by targeting CYP7A1 - Ruijie Gong; Xiaofei Lv; Fengqiong Liu (Cellular & Molecular Biology Letters, 2018)
Abstract Background The miRNA cluster miR-17-92 is known to act as an oncogene in various cancers. Members of this cluster were also found to be involved in some other pathological process, such as steatosis, which is a pivotal event in the initiation and progression of nonalcoholic fatty liver disease (NAFLD). This study aimed to explore whether miR-17, one of the most functional miRNAs in the miR-17-92 family, participates in the process of steatosis in hepatoma cells. Methods We developed both a miR-17-expressing transgenic mouse model and a miR-17-expressing HepG2 cell model, the latter was established via stable transfection. Real-time PCR and western blot were applied to measure the expression levels of miR-17 and the potential target gene CYP7A1. The luciferase assay was used to confirm direct binding of miR-17 and CYP7A1. The oleic acid induction assay and Oil-Red-O staining were performed to support the determination of steatotic changes in HepG2 cell. Results Extensive steatotic changes were observed in the livers of transgenic mice. Fewer were seen in the wild-type animals. CYP7A1 was confirmed as a target gene of miR-17, and the expression of CYP7A1 was found to be negatively regulated in both the transgenic mice liver cells and the miR-17-expressing HepG2 cells. CYP7A1 was found to participate in miR-17-induced steatosis, as its repressed expression in miR-17 HepG2 cells exacerbated steatotic change. Re-introduction of CYP7A1 into miR-17 HepG2 cell partially alleviated steatosis. Conclusions miR-17 is a novel regulator of CYP7A1 signaling in hepatic lipid metabolism, suggesting a potential therapeutic approach for fatty liver.